2015
DOI: 10.1515/bhk-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics Scholar Citations across Academic Ranks

Abstract: SummaryStudy aim: citations to the publications of a scholar have been used as a measure of the quality or influence of their research record. A world-wide descriptive study of the citations to the publications of biomechanics scholars of various academic ranks was conducted. Material and methods: Google Scholar Citations was searched for user profiles reporting "biomechanics" as an interest area and data recorded if they had at least one citation to their publications. Total citations, academic rank, and coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(38 reference statements)
2
1
0
Order By: Relevance
“…The GS citation values in the current study (Table 1) were consistent with previous bibliometric research in biomechanics and sports biomechanics. The median GS C in the present study (1,794) was similar to the median GS C for professor rank biomechanics faculty worldwide [15]. The median 2,784 GS C in the current study also corresponds to about the 70-80% percentile of international biomechanics scholars with GS Profiles [15] and the median estimated GS C (3,000 to 5,000) at the time of receipt of national or international career awards in sports biomechanics [18].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The GS citation values in the current study (Table 1) were consistent with previous bibliometric research in biomechanics and sports biomechanics. The median GS C in the present study (1,794) was similar to the median GS C for professor rank biomechanics faculty worldwide [15]. The median 2,784 GS C in the current study also corresponds to about the 70-80% percentile of international biomechanics scholars with GS Profiles [15] and the median estimated GS C (3,000 to 5,000) at the time of receipt of national or international career awards in sports biomechanics [18].…”
Section: Discussionsupporting
confidence: 76%
“…It was hypothesized that there would be very strong associations of RG RIS with usage metrics, but moderate associations with prestige metrics. This study expands our understanding of RG RIS, usage and prestige metrics for individual researchers; as well as the initial work on citation patterns of biomechanics scholars across academic rank [15] and related to prestigious awards [16,17,18].…”
Section: Introductionmentioning
confidence: 68%
“…The substantial number of subdisciplines and skew to citation data limited the data analysis to descriptive observations, however this does not invalidate the trends in scholarly usage of kinesiology subdiscipline research observed in this study that were consistent with previous research on citations in kinesiology (Knudson, 2014;2015a2015b, 2022a. Extensive research has documented high skews and uncited articles in most all fields, so focus on top percentiles of cited research is most relevant approach to study usage of scholarly research (Bornmann & Marx, 2014;Leydesdorff & Bornmann, 2011;Leydesdorff & Opthof, 2010;Owlia et al, 2011;Knudson, 2015aKnudson, , 2015cKnudson, , 2019bKnudson, , 2022aSeglen, 1992;Stern, 1990). The not time-controlled nature of GS, investigator subjectivity in classifying GS profiles as kinesiologyaffiliated, and user profile variation noted above make it impossible to directly replicate this study.…”
Section: Discussionsupporting
confidence: 66%